2021
DOI: 10.1093/fampra/cmaa128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a very low-cost intervention to increase practices’ engagement with data and change prescribing behaviour: a randomized trial in English primary care

Abstract: Background Unsolicited feedback can solicit changes in prescribing. Objectives Determine whether a low-cost intervention increases clinicians’ engagement with data, and changes prescribing; with or without behavioural science techniques. Methods Randomized trial (ISRCTN86418238). The highest prescribing practices in England for broad-spectrum antibiotics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Internationally, large-scale primary care trials of prescribing feedback aiming to reduce total antibiotic use have typically had limited effects, 7–9 , 11 , 12 although one intervention found that added ‘behavioural impact optimization’ had marginal benefit. 8 An Irish intervention achieved a 2%–3% reduction in total prescribing, 10 a similar effect size to the larger English study targeting the highest prescribing practices, 14 but it only included a small number of volunteer practices. Prescribing feedback trials aiming to improve the choice of antibiotic for specific clinical indications in primary care, typically UTI, 13 , 27 , 28 RTI 29–31 or both, 32 , 33 report larger effect sizes of up to 20%.…”
Section: Discussionmentioning
confidence: 89%
“…Internationally, large-scale primary care trials of prescribing feedback aiming to reduce total antibiotic use have typically had limited effects, 7–9 , 11 , 12 although one intervention found that added ‘behavioural impact optimization’ had marginal benefit. 8 An Irish intervention achieved a 2%–3% reduction in total prescribing, 10 a similar effect size to the larger English study targeting the highest prescribing practices, 14 but it only included a small number of volunteer practices. Prescribing feedback trials aiming to improve the choice of antibiotic for specific clinical indications in primary care, typically UTI, 13 , 27 , 28 RTI 29–31 or both, 32 , 33 report larger effect sizes of up to 20%.…”
Section: Discussionmentioning
confidence: 89%
“…Implementation of social norm feedback varied between studies (figure 2). Social norm feedback was most commonly: sent to all prescribers (n=11)34 37 40–42 45 46 48 as opposed to the highest prescribers only35 36 38 39 47 50 51; and compared prescribing to the group average (n=12) 34–36 38 40 41 45 47 48 50. Only four studies used an injunctive norm, which also provided positive reinforcement to those performing well 41 44 46 52.…”
Section: Resultsmentioning
confidence: 99%
“…The effect sizes of social norm feedback interventions on the number of antibiotics/1000 consultations (n=3) ranged from no change45 to a reduction of 13.6% (95% CI 16.6 to 10.6) at 6 months postintervention35; and the number of antibiotic prescriptions/1000 registered population (n=5) from no change51 to an approximate 5% reduction (−58.7/1000 population (95% CI 116.7 to 0.7)) 12-month postintervention 36…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations